Halobenzene additive modified gel polymer electrolyte as well as preparation method and application thereof

By introducing halide-benzene additives into gel polymer electrolytes, the problems of electrode surface instability and metal dendrites in alkali metal batteries are solved, and the battery cycle stability is improved. Environmentally friendly electrolyte preparation is achieved.

CN119253043APending Publication Date: 2025-01-03GUANGDONG UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411146330.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The application of gel polymer electrolytes in alkali metal batteries has problems such as unstable electrolytes on the surface of high-voltage cathode and uncontrolled growth of anode metal dendrites, which affects the cycling stability of the battery.

Method used

The halobenzene additive is introduced into the gel polymer electrolyte matrix to form a halide-rich electrode-electrolyte interface film. By forming a stable interface film between the electrode and the electrolyte, it alleviates the poor contact between the solid-solid interface and improves the stability of the battery cycle .

Benefits of technology

Significantly accelerate the kinetics of Li+/Na+ in the electroplating and peeling process, reduce the side reaction between metal electrodes and electrolyte solvents/salts, improve battery cycle stability, and reduce the generation of organic waste gas and waste liquids during the electrolyte preparation process, realizing Environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119253043A_ABST
    Figure CN119253043A_ABST
Patent Text Reader

Abstract

The invention discloses a halobenzene additive modified gel polymer electrolyte and a preparation method and application thereof, and the preparation method comprises the following steps: A, mixing a polymer monomer, a halobenzene additive, a free radical polymerization initiator, an organic solvent and alkali metal salt, and stirring to obtain a precursor solution; b, dropwise adding the precursor solution into a fiber membrane, and heating and polymerizing to obtain a halobenzene additive modified gel polymer electrolyte; in the step A, the addition amount of the halobenzene additive is less than or equal to 2 parts in 100 parts of the precursor solution by mass, and the alkali metal salt is any one of a lithium salt and a sodium salt. According to the scheme, the halobenzene additive is introduced into the gel polymer electrolyte matrix, so that the formation of a halide-rich electrode-electrolyte interface film is facilitated, and the problem caused by poor solid-solid interface contact can be effectively relieved, thereby improving the cycle stability of the battery and overcoming the defects in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of quasi-solid-state alkali metal batteries, and in particular to a halobenzene additive-modified gel polymer electrolyte and a preparation method and application thereof. Background Art

[0002] The rapid development of science and technology and the surge in population have led to an explosive growth in energy demand, which in turn has exacerbated the energy crisis. At present, thermal power generation is still the main way of energy supply. However, this method relies on non-renewable resources such as coal, and the environmental problems caused by it are becoming increasingly prominent. Therefore, it is necessary to develop new energy and energy storage systems that are sustainable, clean, efficient and low-cost. Traditional lithium-ion batteries have many advantages such as environmental friendliness, no memory effect and long cycle life, and have already occupied a place in the 3C consumer market. However, during use, current lithium-ion batteries have many potential safety issues such as system thermal runaway and leakage.

[0003] Based on the current challenges, quasi-solid-state alkali metal batteries have attracted widespread attention from scientific researchers due to their advantages of no leakage and high safety. Some studies have pointed out that compared with liquid electrolytes, solid electrolytes show greater advantages in the development of alkali metals and other high-capacity positive electrode materials. According to the state of the system, solid electrolytes are divided into polymer solid electrolytes, inorganic solid electrolytes, and organic-inorganic composite solid electrolytes. Current research shows that polymer solid electrolytes have the advantages of good processability, good elasticity, good contact interface with electrode materials, and high safety, and are solid electrolyte systems with practical potential. Polymer solid electrolyte systems can be divided into two categories-gel polymer electrolytes and all-solid polymer electrolytes. For gel polymer electrolytes, a certain amount of electrolyte is stored in its three-dimensional network structure; therefore, gel polymer electrolytes can be compatible with the multiple advantages of liquid and solid electrolytes, and can better meet the charging and discharging requirements of batteries.

[0004] However, there are still two serious difficulties in the application of gel polymer electrolytes in alkali metal batteries: unstable electrolyte on the high-voltage cathode surface and uncontrolled growth of anode metal dendrites. In order to solve these problems, researchers have made great efforts in adjusting the electrolyte components and electrode surface. Among them, electrolyte component adjustment is considered to be a simple and effective method. Previous studies have shown that electrolyte components not only affect viscosity, ion dissociation and conductivity, but also affect the growth of electrode-electrolyte interface film (CEI / SEI). A stable electrode-electrolyte interface film helps to reduce side reactions between electrodes and electrolytes and improve battery cycle stability. Summary of the invention

[0005] The purpose of the present invention is to propose a halobenzene additive modified gel polymer electrolyte and a preparation method and application thereof. The introduction of halobenzene additives into the gel polymer electrolyte matrix helps to form a halide-rich electrode-electrolyte interface film, which can effectively alleviate the problems caused by poor solid-solid interface contact, thereby improving the battery cycle stability and overcoming the shortcomings of the prior art.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] A method for preparing a halobenzene additive modified gel polymer electrolyte comprises the following steps:

[0008] A. mixing a polymer monomer, a halogenated benzene additive, a free radical polymerization initiator, an organic solvent and an alkali metal salt, and stirring to obtain a precursor solution;

[0009] B. adding the precursor solution dropwise to the fiber membrane and heating and polymerizing to obtain a halobenzene additive-modified gel polymer electrolyte;

[0010] In step A, the amount of the halobenzene additive added is ≤2 parts in 100 parts of the total amount of the precursor solution, and the alkali metal salt is any one of a lithium salt and a sodium salt.

[0011] Preferably, in step A, the precursor solution, calculated by weight, includes 5 to 30 parts of polymer monomer, 1 part of halobenzene additive, 0.01 to 1 part of free radical polymerization initiator, 70 to 95 parts of organic solvent and 10 to 20 parts of alkali metal salt in a total amount of 100 parts.

[0012] Preferably, in step B, the amount of the precursor solution added is 100 to 200 μl.

[0013] Preferably, in step B, the heating temperature of the heating polymerization is 60-70° C., and the heating time is 6-12 hours.

[0014] Preferably, in step A, the halogenated benzene additive is any one of fluorobenzene and its derivatives, iodobenzene and its derivatives, bromobenzene and its derivatives, and chlorobenzene and its derivatives.

[0015] Preferably, in step A, the polymer monomer is an acrylic ester monomer.

[0016] Preferably, in step A, the free radical polymerization initiator is an azo compound.

[0017] Preferably, in step A, the organic solvent is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate and methyl ethyl carbonate.

[0018] A halobenzene additive modified gel polymer electrolyte is prepared by using the halobenzene additive modified gel polymer electrolyte preparation method.

[0019] An alkali metal battery uses the halobenzene additive to modify the gel polymer electrolyte.

[0020] The technical solution provided by the present invention may include the following beneficial effects:

[0021] 1. This scheme introduces halogenated benzene additives into the gel polymer electrolyte matrix to form a halide-rich electrode-electrolyte interface film between the electrode and the electrolyte, which can effectively alleviate the problems caused by poor solid-solid interface contact and improve the battery cycle stability. Since lithium halide and sodium halide are beneficial components for building a stable electrode-electrolyte interface film, a stable and uniform halide-rich SEI layer is formed on the surface of the alkali metal anode, which can significantly accelerate the Li + / Na + Kinetics of plating and stripping processes, reducing side reactions between metal electrodes and electrolyte solvents / salts.

[0022] 2. The gel polymer electrolyte of this scheme is formed in situ from a precursor solution containing a halogenated benzene additive, which can avoid the generation of a large amount of organic waste gas and waste liquid during the electrolyte preparation process, thereby achieving environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is the electrochemical stability test curve of IB-GPE obtained in Example 1 of the present invention;

[0024] Figure 2 This is a cyclic voltammetric test curve of a NCM811||Li battery assembled with IB-GPE obtained in Example 1 of the present invention;

[0025] Figure 3 This is a constant current charge and discharge test curve of a NCM811||Li battery assembled with the IB-GPE obtained in Example 1 of the present invention;

[0026] Figure 4 This is the electrochemical stability test curve of TFBB-GPE obtained in Example 2 of the present invention;

[0027] Figure 5 This is a cyclic voltammetric test curve of an NVP||Na battery assembled with TFBB-GPE obtained in Example 2 of the present invention;

[0028] Figure 6 This is a constant current charge and discharge test curve of an NVP||Na battery assembled with TFBB-GPE obtained in Example 2 of the present invention. DETAILED DESCRIPTION

[0029] A method for preparing a halobenzene additive modified gel polymer electrolyte comprises the following steps:

[0030] A. mixing a polymer monomer, a halogenated benzene additive, a free radical polymerization initiator, an organic solvent and an alkali metal salt, and stirring to obtain a precursor solution;

[0031] B. adding the precursor solution dropwise to the fiber membrane and heating and polymerizing to obtain a halobenzene additive-modified gel polymer electrolyte;

[0032] In step A, the amount of the halobenzene additive added is ≤2 parts in 100 parts of the total amount of the precursor solution, and the alkali metal salt is any one of a lithium salt and a sodium salt.

[0033] In order to form a stable interface film at the electrode-electrolyte interface, so as to reduce the side reactions between the electrode and the electrolyte, and thus improve the cycle stability of the battery, this technical solution proposes a preparation method of a halobenzene additive-modified gel polymer electrolyte, and introduces a halobenzene additive into the gel polymer electrolyte matrix to form a halide-rich electrode-electrolyte interface film between the electrode and the electrolyte, which can effectively alleviate the problems caused by the poor solid-solid interface contact and improve the battery cycle stability. It should be noted that lithium halides (such as lithium fluoride, lithium chloride, lithium iodide, etc.) and sodium halides (such as sodium fluoride, lithium bromide, sodium iodide, etc.) are beneficial components for constructing a stable electrode-electrolyte interface film, forming a stable and uniform halide-rich SEI layer on the surface of the alkali metal anode, which can significantly accelerate the Li + / Na + Kinetics of plating and stripping processes, reducing side reactions between metal electrodes and electrolyte solvents / salts.

[0034] In addition, the gel polymer electrolyte of the present scheme is formed in situ from a precursor solution containing a halogenated benzene additive, which can avoid the generation of a large amount of organic waste gas and waste liquid during the electrolyte preparation process, thereby achieving environmental friendliness.

[0035] Preferably, the lithium salt is any one of lithium hexafluorophosphate, lithium perchlorate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide.

[0036] Preferably, the sodium salt is any one of sodium hexafluorophosphate and sodium perchlorate.

[0037] Preferably, in step B, the fiber membrane is any one of a glass fiber membrane, a polyethylene membrane, a polyethylene membrane, a polypropylene membrane, a polyvinylidene fluoride static membrane and a polyvinylidene fluoride-co-hexafluoropropylene membrane.

[0038] Further explained, in step A, calculated by weight, the total amount of 100 parts of the precursor solution includes 5 to 30 parts of polymer monomers, 1 part of halobenzene additive, 0.01 to 1 part of free radical polymerization initiator, 70 to 95 parts of organic solvent and 10 to 20 parts of alkali metal salt.

[0039] Specifically, this scheme also optimizes the formula of the precursor solution. Among them, the polymer monomer is used to construct the skeleton of the three-dimensional polymer, and then store the organic liquid. If the amount is too little, it is not conducive to the gel electrolyte film formation. If the amount is too large, it is not conducive to the transmission of ions. The halogenated benzene additive is used to optimize the interfacial film components in the battery and improve the stability of the interfacial film. The free radical polymerization initiator is used to initiate the free radical polymerization reaction of the polymer monomer. If the amount is too low. It will lead to incomplete polymerization, which is not conducive to the electrolyte film formation. If the amount is too large, it may cause harmful side reactions. The organic solvent is used for ion transmission. If the amount is too low, it will lead to a decrease in battery performance. If the amount is too high, it will be not conducive to the gel electrolyte film formation. Further, when selecting the amount of organic solvent, the relationship between the amount of organic solvent and the battery performance should be weighed under the premise of ensuring the gel electrolyte film formation. The amount of organic solvent should be reduced as much as possible under the condition of ensuring the battery performance to improve the battery safety performance. Alkali metal salts are used to provide alkali metal ions.

[0040] Further, in step B, the amount of the precursor solution added is 100 to 200 microliters. To fully wet the fiber membrane, the amount of the precursor solution should be no less than 100 microliters; however, if the amount of the precursor solution exceeds 200 microliters, the excess precursor solution will overflow when the battery is sealed, causing waste.

[0041] To further illustrate, in step B, the heating temperature of the heating polymerization is 60-70° C., and the heating time is 6-12 hours.

[0042] In order to effectively initiate free radical reactions inside the battery and initiate the precursor solution to form a gel polymer electrolyte inside the battery, the present solution also optimizes the temperature and time in the heating polymerization step.

[0043] Preferably, in step B, the heating temperature of the heating polymerization is 60° C. and the heating time is 12 h.

[0044] To further illustrate, in step A, the halogenated benzene additive is any one of fluorobenzene and its derivatives, iodobenzene and its derivatives, bromobenzene and its derivatives, and chlorobenzene and its derivatives.

[0045] To further illustrate, in step A, the polymer monomer is an acrylic ester monomer.

[0046] In order to effectively establish a three-dimensional polymer network through free radical polymerization reaction, thereby blocking the organic solvent, the present scheme preferably uses acrylic acid ester monomers as polymer monomers of the electrolyte.

[0047] Preferably, the polymer monomer includes at least one of isopentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate, bisphenol A ethoxylated diacrylate, tetraethylene glycol dimethacrylate, triethylene glycol diacrylate, dipentaerythritol pentaacrylate, polyethylene glycol methyl ether acrylate, polyethylene glycol diacrylate, polyethylene glycol methyl ether methacrylate and polyethylene glycol dimethacrylate.

[0048] To further illustrate, in step A, the free radical polymerization initiator is an azo compound.

[0049] In this scheme, azo compounds are preferably used as free radical polymerization initiators of electrolytes. On the one hand, they have no oxygen-containing byproducts and the reaction initiation conditions are relatively mild. On the other hand, they are cheap and easy to obtain.

[0050] Preferably, the free radical polymerization initiator is azobisisobutyronitrile.

[0051] To further illustrate, in step A, the organic solvent is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate and methyl ethyl carbonate.

[0052] The types of organic solvents selected in this scheme cover common commercial electrolytes on the market, which helps to verify the applicability of additives in existing electrolyte systems.

[0053] A halobenzene additive modified gel polymer electrolyte is prepared by using the halobenzene additive modified gel polymer electrolyte preparation method.

[0054] The technical solution further proposes a halobenzene additive-modified gel polymer electrolyte prepared by the above method, which can effectively alleviate the problems caused by poor solid-solid interface contact.

[0055] An alkali metal battery uses the halobenzene additive to modify the gel polymer electrolyte.

[0056] The technical solution also proposes an alkali metal battery using a halobenzene additive-modified gel polymer electrolyte prepared by the above-mentioned preparation method, which is beneficial to the formation of a halide-rich interface film between the electrolyte and the electrode material, thereby improving the battery cycle stability.

[0057] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0058] Example 1

[0059] A. Mix isopentaacrylate monomer, iodobenzene, azobisisobutyronitrile, an organic solvent (a mixed solvent of ethylene carbonate and methyl ethyl carbonate in a volume ratio of 1:1) and lithium hexafluorophosphate, and stir to obtain a precursor solution; wherein, calculated by mass, the precursor solution with a total amount of 100 parts includes 5 parts of isopentaacrylate monomer, 1 part of iodobenzene, 0.01 parts of azobisisobutyronitrile, 83.99 parts of organic solvent and 10 parts of lithium hexafluorophosphate.

[0060] B. In an argon-filled glove box with moisture <0.1ppm and oxygen <0.1ppm, the lithium sheet, ternary nickel-cobalt-manganese positive electrode sheet, steel sheet, and spring sheet required for assembling button batteries are placed in the negative electrode shell in sequence, a polyvinylidene fluoride-co-hexafluoropropylene film (i.e., PVDF-HFP film) is placed on the surface of the lithium sheet, and the precursor solution is dripped onto the PVDF-HFP film; wherein, the amount of the precursor solution dripped is 180 μL;

[0061] After the precursor solution fully infiltrates the PVDF-HFP membrane, place the ternary nickel-cobalt-manganese cathode sheet (the mass ratio of nickel, cobalt, and manganese elements is 8:1:1, i.e., NCM811) and the cathode shell;

[0062] The sealed button cell was taken out from the argon-filled glove box and heated to initiate the in-situ polymerization reaction of the precursor solution, generate a gel polymer electrolyte with good interfacial compatibility, and prepare a NCM811||Li battery with a gel polymer electrolyte, denoted as IB-GPE. The heating temperature was 60°C and the heating time was 12h.

[0063] The IB-GPE obtained in Example 1 was subjected to an electrochemical stability window test using a lithium-steel battery to obtain an electrochemical stability test curve, as shown in FIG. Figure 1 As shown, the electrochemical stability window value of the prepared IB-GPE is above 4.5V.

[0064] At the same time, the NCM811||Li battery assembled with IB-GPE obtained in Example 1 was subjected to cyclic voltammetry test and charge-discharge cycle test. The test results are as follows: Figure 2 , 3 shown. Figure 2 The test results show that each cycle presents three pairs of redox peaks, corresponding to Ni 2+ / Ni 4+ and Co 3+ / Co 4+ It can be found that after the first activation cycle, the three groups of redox peaks have a high overlap, which indicates that the battery system has high reversibility and good electrochemical activity. Figure 3 The test results show that: at room temperature, at a 3C rate (1C = 200mAh g -1) After 650 cycles of constant current charge and discharge, the retention capacity is 131.3 mAh g -1 , the retention rate is 74.39%.

[0065] Example 2

[0066] A. Mix a polymer monomer (a mixed monomer in which polyethylene glycol diacrylate monomer and polybisphenol A ethoxylated diacrylate monomer are mixed in a mass ratio of 5:1), 1,4-dibromotetrafluorobenzene (TFBB), azobisisobutyronitrile, an organic solvent (a mixed solvent in which ethylene carbonate and propylene carbonate are mixed in a mass ratio of 1:2 to obtain an intermediate solution, and then 2 wt% of fluoroethylene carbonate is added to the intermediate solution to mix), and sodium hexafluorophosphate, and stir to obtain a precursor solution; wherein, calculated by mass, the precursor solution in a total amount of 100 parts includes 10 parts of polymer monomer, 1 part of 1,4-dibromotetrafluorobenzene, 0.01 part of azobisisobutyronitrile, 78.99 parts of organic solvent, and 10 parts of sodium hexafluorophosphate.

[0067] B. In an argon-filled glove box with moisture <0.1ppm and oxygen <0.1ppm, the sodium sheet, sodium vanadium fluorophosphate positive electrode sheet (NVP), steel sheet, and spring sheet required for assembling button batteries are placed in the negative electrode shell in sequence, a glass fiber membrane (GF membrane) is placed on the surface of the sodium sheet, and the precursor solution is dripped onto the GF membrane; wherein, the amount of the precursor solution dripped is 160 μL;

[0068] After the precursor solution fully soaks the GF membrane, place the NVP and cathode shell;

[0069] The sealed button cell was taken out from the argon-filled glove box and heated to initiate the in-situ polymerization reaction of the precursor solution, generate a gel polymer electrolyte with good interfacial compatibility, and prepare an NVP||Na battery with a gel polymer electrolyte, denoted as TFBB-GPE. The heating temperature was 60°C and the heating time was 12h.

[0070] The TFBB-GPE obtained in Example 2 was subjected to an electrochemical stability window test using a lithium-steel battery to obtain an electrochemical stability test curve, as shown in FIG. Figure 4 As shown, the electrochemical stability window value of the prepared TFBB-GPE reaches 4.85V.

[0071] At the same time, the TFBB-GPE assembled NVP||Na battery obtained in Example 2 was subjected to cyclic voltammetry test and charge-discharge cycle test. The test results are as follows: Figure 5 , 6 shown. Figure 5 The test results show that: +The deposition and stripping correspond to a pair of redox peaks on the CV curve. The CV curve after activation shows a large overlap and a small potential difference, indicating that the battery has high electrochemical reversibility. Figure 6 The test results show that at room temperature, the retention capacity is 86.60 mAh g after 1600 cycles of charge and discharge at a constant current rate of 1C. -1 , the retention rate is 85.10%.

[0072] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A method for preparing a halogenated benzene additive modified gel polymer electrolyte, characterized in that: The following steps are involved: A. mixing a polymer monomer, a halogenated benzene additive, a free radical polymerization initiator, an organic solvent and an alkali metal salt, and stirring to obtain a precursor solution; B. adding the precursor solution dropwise to the fiber membrane and heating and polymerizing to obtain a halobenzene additive-modified gel polymer electrolyte; In step A, the amount of the halobenzene additive added is ≤2 parts in 100 parts of the total amount of the precursor solution, and the alkali metal salt is any one of a lithium salt and a sodium salt.

2. The method for preparing a halogenated benzene additive modified gel polymer electrolyte according to claim 1, characterized in that: In step A, the precursor solution, calculated by weight, includes 5 to 30 parts of polymer monomer, 1 part of halobenzene additive, 0.01 to 1 part of free radical polymerization initiator, 70 to 95 parts of organic solvent and 10 to 20 parts of alkali metal salt in a total amount of 100 parts.

3. The method for preparing a halobenzene additive modified gel polymer electrolyte according to claim 1, characterized in that: In step B, the amount of the precursor solution added is 100 to 200 μl.

4. The method for preparing a halobenzene additive modified gel polymer electrolyte according to claim 1, characterized in that: In step B, the heating temperature of the heating polymerization is 60-70° C., and the heating time is 6-12 hours.

5. The method for preparing a halobenzene additive modified gel polymer electrolyte according to claim 1 or 2, characterized in that: In step A, the halogenated benzene additive is any one of fluorobenzene and its derivatives, iodobenzene and its derivatives, bromobenzene and its derivatives, and chlorobenzene and its derivatives.

6. The method for preparing a halobenzene additive modified gel polymer electrolyte according to claim 1 or 2, characterized in that: In step A, the polymer monomer is an acrylic ester monomer.

7. The method for preparing a halobenzene additive modified gel polymer electrolyte according to claim 1 or 2, characterized in that: In step A, the free radical polymerization initiator is an azo compound.

8. The method for preparing a halobenzene additive modified gel polymer electrolyte according to claim 1 or 2, characterized in that: In step A, the organic solvent is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate and methyl ethyl carbonate.

9. A halogenated benzene additive modified gel polymer electrolyte, characterized in that: The invention is prepared by using the preparation method of the halobenzene additive modified gel polymer electrolyte according to any one of claims 1 to 8.

10. An alkali metal battery, characterized in that: The gel polymer electrolyte is modified by using the halobenzene additive as claimed in claim 9.

Citation Information

Patent Citations

  • Composition for gel polymer electrolyte, gel polymer electrolyte prepared therefrom, and lithium secondary battery comprising same

    CN110603681A

  • Preparation method of gel polymer electrolyte, gel polymer electrolyte and application

    CN115621545A

  • Composition for gel polymer electrolyte and lithium secondary battery comprising gel polymer electrolyte formed therefrom

    CN115917823A

  • Gel polymer electrolyte and lithium secondary battery

    JP2005235683A

  • Lithium polymer battery

    US20110262815A1